1977
DOI: 10.1111/j.1469-8986.1977.tb01186.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Degeneration and Cardiac Arrest in Squirrel Monkey: Physiological and Psychological Correlates

Abstract: Behavioral factors and cardiovascular changes associated with myocardial degeneration and cardiac arrest induced by shock avoidance stress were studied. Pairs of avoidance and yoked squirrel monkeys were exposed to a 24‐hr session. Myocardial degeneration and cardiac arrest were more readily induced in avoidance than yoked monkeys. The cardiac lesions were not related to body weight, aggressive behavior, or number of shocks received during stress, but an increased heart rate without hypertension during the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The physiological meaning of heart arrests concomitant with startle could be absolutely different from that of cardiovascular adaptations over a period of hours or days. On the other hand, both CA and longterm stress can lead to cardiac dysfunctions caused by a lack of circulation in the former case and by myocardial degeneration (Corley, Mauck, & Shiel, 1975;Corley, Mauck, Shiel, Barber, Clark, & Blocher, 1979;Corley, Shiel, Mauck, Clark, & Barber, 1977;Mascitelli-Coriandolli, 1958;Raab, Chaplin, & Bajusz, 1964) involving hormonal factors in the latter. Only nervous regulation is thought to be responsible for CA.…”
Section: Experimental Data From Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological meaning of heart arrests concomitant with startle could be absolutely different from that of cardiovascular adaptations over a period of hours or days. On the other hand, both CA and longterm stress can lead to cardiac dysfunctions caused by a lack of circulation in the former case and by myocardial degeneration (Corley, Mauck, & Shiel, 1975;Corley, Mauck, Shiel, Barber, Clark, & Blocher, 1979;Corley, Shiel, Mauck, Clark, & Barber, 1977;Mascitelli-Coriandolli, 1958;Raab, Chaplin, & Bajusz, 1964) involving hormonal factors in the latter. Only nervous regulation is thought to be responsible for CA.…”
Section: Experimental Data From Vertebratesmentioning
confidence: 99%
“…Yoked monkeys not allowed to predict or control electroshock exhibited severe bradycardia that led to ventricular arrests (Corley, Shiel, Path, Mauck, & Greenhoot, 1973;Corley et aI. , 1975;Corley et aI., 1979;Corley et al, 1977. ) In a pioneer study by Richter (1957) inspired by earlier work by Cannon (1942), sudden deaths of wild rats held in the hand or put into water were reported.…”
Section: Experimental Data From Vertebratesmentioning
confidence: 99%
“…1). Studies concerned with triggers of coronary artery disease are increasing lately and physical exertion has been found to be a serious trigger for AMI onset [18]. Another study which investigated all kinds of daily activities including mental and psychological ones revealed that psychological exertion has the same effect as physical exertion in triggering myocardial ischemic episodes in coronary artery patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…Another study which investigated all kinds of daily activities including mental and psychological ones revealed that psychological exertion has the same effect as physical exertion in triggering myocardial ischemic episodes in coronary artery patients [19]. Evidence from psychophysiologic studies with squirrel monkeys reveals that within only a 24-hour session stress-induced myocardial changes and death were related to autonomic disturbances precipitated by psychological stress [18]. …”
Section: Discussionmentioning
confidence: 99%
“…The essential elements include: (i) avoidance task perform ance, (ii) physically aversive exposure (to glare), (iii) uncertainty (due to dimin ished visibility), (iv) conflicting forces acting upon the level of arousal (darkness plus circadian factors diminish arousal, glare exposure plus driving task demands increase arousal), (v) abrupt changes in oculomotor autonom ic reflexes which involve sympathetic and parasympathetic branches and conflict between the central and refle x tendencies. The first three elements have been associated with a lowered threshold for ventricular fibrillation and with sudden cardiac death in experimental animals (84,86,140). The abrupt change s mentioned in the fifth element could disrupt neuroregulation of the autonomic nervous system and, as seen in clinical and experimental studies, increase cardiac electrical instability (141)(142)(143).…”
Section: Model F or Increased Cardiac Vulnerability Caused By Visuallmentioning
confidence: 99%